Tunable bright interlayer excitons in few-layer black phosphorus based van der Waals heterostructures. (25th September 2018) - Chen, Yifeng; Quek, Su Ying
Abstract: Few-layer black phosphorus (BP) is a direct band gap material with large exciton binding energies, and shows great promise in optoelectronic applications. Here, we study the excitons in BP-based heterostructures with encapsulation and spacer 2D layers, using first principles GW and Bethe–Salpeter equation (BSE) methods. The 2D layers chosen are germanium sulfide (GeS) and hexagonal boron nitride (hBN), representing respectively strong and weak hybridization with BP. Except for hBN-encapsulated BP, all systems host bright interlayer (or indirect) excitons. In contrast to 2D indirect gap heterostructures, the interlayer excitons here are much brighter. Strong hybridization between GeS and BP increases the effective mass and room temperature exciton lifetimes. In contrast, the hBN spacer layer decouples the BP monolayers in BP/hBN/BP, resulting in the lowest energy exciton being dark. Surprisingly, however, BP/hBN/BP hosts interlayer BP excitons that are even brighter than those in bilayer BP. This lowest energy bright exciton lies very close in energy to the dark state, resulting in an increased effective lifetime. Our work uncovers the interplay between interlayer interactions and the physics of interlayer excitons, and paves the way for the use of bottom-up materials design to optimize the dipole oscillator strengths and lifetimes of interlayer excitons for excitonic device applications.